Determination of flavones in species of Thymus L. (Lamiaceae) from Macedonian flora - Svetlana Kulevanova; Marina Stefova; Tatjana Kadifkova Panovska; Jasmina Tonic; Trajce Stafilov (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2002)
Assay of flavonoids in extracts of seven Thymus L. (Lamiaceae) species from Macedonia including identification and quantification was performed. Extracts obtained after hydrolysis of air dried samples (A1) were analyzed by thin layer chromatography (TLC) and high performance liquid chromatography (HPLC). Luteolin and apigenin were identified in comparison to authentic standard substances. The content of total flavonoids in plant samples determined by UV-Vis spectrometry (with AlCl3) ranged from 0.05-0.13 %. Two other extracts were prepared by extraction with a mixture of ethanol:water (7:3, V/V), evaporation until only water remained and extraction first with diethylether (A2) and secondly with ethyl acetate (A3). The content of flavonoids in diethyl-ether and ethyl acetate extracts ranged from 52.5-244.4 mg·ml-1 and 48.7 -117.5 mg·ml-1, respectively. For quantification of luteolin and total flavonoids the HPLC method was applied, using reverse phase column C18, mobile phase consisting of 5% acetic acid and methanol in gradient elution mode and column temperature set to 40 oC. The content of luteolin in the plant samples ranged from 0.23-0.48 % (m/m), while the content of total flavonoids was found to be 0.26-0.52 %.